Magnitudes and capital key divergence of the Eurosystem's PSPP/PEPP purchases - update June 2022: study supported by the Brigitte Strube Foundation - Birkholz, Carlo; Heinemann, Friedrich (ZEW-Kurzexpertise, 2022)
The ECB is about to discontinue its net asset purchases. In December 2021, the ECB Council had already decided to end net purchases under the Pandemic Emergency Purchase Programme (PEPP) by the end of March 2022. Given the very high and persistent inflation, recent remarks from ECB board members indicate that the decision to also discontinue the Asset Purchase Programme (APP) is imminent. The APP includes the Public Sector Purchase Programme (PSPP) as its most important component. Ending all net purchases will then pave the way for a first increase of the key ECB interest rates.
Keywords: Graue Literatur